Photoluminescence of BaZrO3 explained by a order/disorded transformation - Aguiar, E. C.; Simoes, A. Z. [UNESP]; Paskocimas, C. A.; Cilense, M. [UNESP]; Longo, E. [UNESP]; Varela, J. A. [UNESP] (Springer, 2015)
A hydrothermal (HTMW) microwave method was used to synthesize ordered-disordered BaZrO3 (BZ) nanoparticles at temperature of 140 A degrees C with times ranging from 15 min to 2 h. X-ray diffraction results verified the formation of BZ crystallites at a soaking time of 2 h while infrared data showed no traces of carbonate. Field emission scanning microcopy revealed a homogeneous size distribution of nanometric BZ powders. HTMW produced nanoparticles of pure BZ phase, with a size ranging from 40 to 80 nm. These results are in agreement with Raman scattering values which show that the HTMW synthesis route is rapid and cost effective. This method could be used as an alternative to obtain BZ nanoparticles as compared to other chemical methods. Intense photoluminescence in disordered BZ powders was observed at room temperature. The key of mystery of the intense PL emission is related to order-disorder structural in BZ lattice.